PEMANFAATAN CITRA LANDSAT 8 UNTUK ESTIMASILUAS LAHAN TERBANGUN DAN TIDAK TERBANGUNPADA KOTA BANDUNG - Rachmad Kurniyanto (2020)
Economic development and population growth in the city of Bandung is very rapid at this time, it is possible will cause an imbalance in land use. From the other side to meet the needs of the community, the role of government is needed to pay attention to the continuous city planning so that the quality of life of the community is maintained and there is a balance between the natural and artificial environment. Then we need a system that is able to monitor the development of land use by utilizing the analysis of Geographic Information Systems. This study uses the NDBI (Normalized Difference Built-Up Index) transformation to detect built up land in the city of Bandung.